Improved energy harvesting ability of C3H7NH3PbI3 decorated PVDF nanofiber based flexible nanogenerator. (May 2023) - Sengupta, Payal; Sadhukhan, Priyabrata; Saha, Samik; Das, Sachindranath; Ray, Ruma
Abstract: Propylammonium lead iodide, C3 H7 NH3 PbI3, was synthesized by sol-gel method and incorporated in polyvinylidene difluoride (PVDF) to produce nanofibers by electrospinning technique. These nanofibers possess an improved degree of crystallinity with the successful conversion of non-polar phase to polar phase content. The tensile strength and thermal stability of nanofibers are also enhanced significantly with the addition of C3 H7 NH3 PbI3. The fabricated lightweight, flexible, durable, cost-effective, self-powered piezoelectric nanogenerator is observed to generate 60 V open circuit voltage, 27.5 μA short circuit current, and 9.81 mW/m 2 power under periodic hammering with a free hand. Voltage generation of this nanogenerator scavenging mechanical energy from various sources is also detected. This device exhibits remarkable mechano-sensitivity (∼ 6.3 V/N in the low applied force region and 12.12 V/N in the higher applied force region) with superior energy conversion efficiency ∼ 42.03 %. The flexibility along with ultra-sensitivity of this power generator initiates its utility as wearable nano sensors. Moreover, the ultrafast capacitor charging ability of the nanogenerator assures its potential as a nano-tactile sensor. The optimal energy band gap and photoactive nature of the C3 H7 NH3 PbI3 @PVDF composite confirm its efficacy as a photodetector/diode. Therefore, the proposed C3 H7 NH3 PbI3 @PVDF composite enables to design a multifaceted device that can perform separately/simultaneously as mechanical energy and solar energy harvester. Graphical Abstract: ga1 Highlights: C3 H7 NH3 PbI3 embedded PVDF nanofibers produced by electrospinning technique to get superior piezoelectric response. Flexible, self-powered nanogenerator produces 60 V VOC, 27.5 μA ISC, and 9.81 mW/m 2 power under periodic free hand hammering. Remarkable mechano-sensitivity (∼ 6.3 V/N and 12.12 V/N) with superior energy conversion efficiency ∼ 42.03 % is revealed. The piezo-photo active response of the C3 H7 NH3 PbI3 @PVDF composite confirms its efficacy as a photo-detector.